Estimation of effective moisture diffusivity of Red amaranth leaves (Amaranthus tricolor L.) for thin-layer drying technology - Sultana, A.; Ghosh, U. (International Journal of Agricultural Technology, 2021)
Red amaranth leaves are the excellent source of antioxidant. The chlorinated sample dried at600C gave better quality product. Midilli’s model was found to satisfactorily describe the drying behavior of red amaranth leaves which showed the highest R2value, lowest X2value and RMSE values. The statistical indicators showed that Midilli’s model was the best model to describe the drying kinetics of red amaranth leaves